Identification and Characterization of the Growth-Regulating Factors-Interacting Factors in Cotton - Hu, Daowu; Ge, Yuting; Jia, Yinhua; He, Shoupu; Geng, Xiaoli; Wang, Liru; Pan, Zhaoe; Iqbal, Zubair; Mahmood, Tahir; Li, Hongge; Chen, Baojun; Wang, Xiaoyang; et al. (Frontiers in Genetics, 2022)
Growth-regulating factors-interacting factors (GIFs) are a type of transcription co-activators in plants, playing crucial roles in plants’ growth, development, and stress adaptation. Here, a total of 35 GIF genes were identified and clustered into two groups by phylogenetic analysis in four cotton genus. The gene structure and conserved domain analysis proved the conservative characteristics of GIF genes in cotton. The function of GIF genes was evaluated in two cotton accessions, Ji A-1-7 (33xi) and King, which have larger and smaller lateral root numbers, respectively. The results showed that the expression of GhGIF4 in Ji A-1-7 (33xi) was higher than that in King. The enzyme activity and microstructure assay showed a higher POD activity, lower MDA content, and more giant cells of the lateral root emergence part phenotype in Ji A-1-7 (33xi) than in King. A mild waterlogging assay showed the GIF genes were down-regulated in the waterlogged seedling. Further confirmation of the suppression of GhGIF4 in cotton plants further confirmed that GhGIF4 could reduce the lateral root numbers in cotton. This study could provide a basis for future studies of the role of GIF genes in upland cotton.